2020
DOI: 10.1039/d0tc03348k
|View full text |Cite
|
Sign up to set email alerts
|

Conductive polymer supported and confined iron phosphide nanocrystals for boosting the photocatalytic hydrogen production of graphitic carbon nitride

Abstract: Development of earth abundant cocatalyst with confined size on suitable conductive support was of high importance for facilitating the activity of solar energy conversion using semiconductors. In this work, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Higher photocatalytic efficiency can be achieved for Nb 6 /PPy-RGO composites by the modification with PPy and RGO. It has been reported that conductive polymers can be used as photocatalysts for H 2 production from water splitting [65]. However, in such Nb 6 /PPy-RGO-0.25 composites, pure PPy and RGO cannot exhibit photocatalytic activity due to their combination of electrons and holes.…”
Section: Proposed Photocatalytic Mechanismmentioning
confidence: 99%
“…Higher photocatalytic efficiency can be achieved for Nb 6 /PPy-RGO composites by the modification with PPy and RGO. It has been reported that conductive polymers can be used as photocatalysts for H 2 production from water splitting [65]. However, in such Nb 6 /PPy-RGO-0.25 composites, pure PPy and RGO cannot exhibit photocatalytic activity due to their combination of electrons and holes.…”
Section: Proposed Photocatalytic Mechanismmentioning
confidence: 99%
“…[ 20–26 ] In particular, applying the perovskite materials for LEDs have become a research focus. [ 27,28 ] The NCs of CsPbX 3 (X = Cl, Br, and I) can emit narrow and strong spectra from exciton. [ 18,24 ] Lead‐free double perovskite material Cs 2 AgInCl 6 :Bi can emit warm white light with one broadband emission peak from STE, its spectrum in the blue region is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35 ] The A 2 BX 6 ‐type phosphor components and single‐phase white phosphors have been used to construct white LEDs. [ 35–40 ] However, the resultant white LEDs, particularly the all‐A 2 BX 6 white LEDs, exhibit insufficient color rendering due to the shortage of red light. [ 41 ] Therefore, to attain high‐color‐rendering all‐A 2 BX 6 white LEDs, it is an urgent need to develop red‐emitting phosphors in the family of A 2 BX 6 perovskite variants.…”
Section: Introductionmentioning
confidence: 99%